Hermeneutic and Heuristic Review of Aina Adzhabu Poetryby Nizar Qobbani: Analisis Semiotik Riffaterre - Dewi, Lusiana Puspa; Yani, Achmad; Susilawati, Ani (Institut Agama Islam Negeri Metro, 2023)
This research examines the poetry of Aina Azhabu by Nizzar Qabani, a Syrian poet. This poem tells about the character I who lost his girlfriend Dariya. However, there are still words and sentences that are difficult for readers to understand. Therefore, this poem is very suitable for analysis using riffaterre semiotic theory. The method used in this research is descriptive qualitative method. The data source used was a book entitled Qasayid Mutawahisha by Nizzar Qabbani, and the data source used was riffaterre semiotic theory, then the data collection technique used was library techniques. In this poem there are many sentences that do not have complete meaning, such as أن نفسي من نفسها تتعجب، يسكن الشعر في حدائق عينيك، فلولا عيناك لا شعر يكتب, which contain a replacement of the meaning of the previous meaning (displacing of meaning). Then to get the complete meaning, you have to use a search matrix, model and hypogram. This model will guide the reader to find the matrix. In the opinion of the author, the model in this poem is in two sentences أنت أحلى خرافة في حياتي و والذي يتبع الخرافات يتعب these two models were chosen, because both of them represent the entire sound of the text of the poem contained in the subject, firstly the poet's unwillingness due to Dariya's departure so that he considers his lover as a mystery in his life, and secondly the idea that his love for my character for Daria is a delusion. The poetry matrix that is then obtained is about “Imagine Love” which can be seen from the use of the word love repeated up to four times. Then in the last line the idea that the love of my character for Daria is just a fantasy.